Cobertura y asociación con variables clínicas de la vacunación antineumocócica en la población mayor de 65 años de Tarragona-Valls - Olga Ochoa Gondar (Revista Española de Salud Pública, 2005)
Background: In Catalonia, a polyanccharide pneumococcalvaccine (PPV) programme which includes subjects over 65 yearsold, was started in 1999. Three years later, we study the vaccinecover in relation to the presence of risk factors for pneumonia.Methods: Cross-sectional observational study conducted in 8Basic Health Areas (BHA) of Tarragona. All the subjects over 65years old and assigned to one of the 8 basic health areas participatingin the study were included (n= 11241). Using computerized clinicalrecords and vaccination records we evaluated whether each patienthad received PPV before January 2002, and the presence of diseaseor risk factors for pneumonia.Results: Global vaccination coverage was 44.4% (37.1% in 65-74 years, 53.9% in 75-84 and 51.5% in 85-99 years). The greatestcoverage was recorded in subjects with active neoplasm (56.7%),chronic necropathy (55.3%), chronic lung disease (54.2%) and chroniccardiopathy (53.5%). The least coverage was recorded in smokers(38.9%), alcoholic patients (43.6%) and chronic liver disease(46.5%). AVP coverage was 38.9% (CI 95%: 37.6-40.2) in subjectswithout any risk factors, 47.7% (CI 95%: 46.1-49.4) in those withone factor, and 52.7% (CI 95%:52.6-54.8) in those with two or morefactors.